2021
DOI: 10.3390/nu14010026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D Supplementation in Children with Autism Spectrum Disorder: A Narrative Review

Abstract: Children with autism spectrum disorder (ASD) present with persistent deficits in both social communication and interactions, along with the presence of restricted and repetitive behaviors, resulting in significant impairment in significant areas of functioning. Children with ASD consistently reported significantly lower vitamin D levels than typically developing children. Moreover, vitamin D deficiency was found to be strongly correlated with ASD severity. Theoretically, vitamin D can affect neurodevelopment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 90 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…Other results showed that the plasma concentration of DBP is significantly reduced in ASD children [ 47 ]. The plasma concentration of vitamin D itself was reported to be reduced in these children [ 13 , 14 , 15 ], with a negative correlation between circulating serum vitamin D concentration and CARS scores, suggesting ASD severity to be associated with vitamin D serum levels [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other results showed that the plasma concentration of DBP is significantly reduced in ASD children [ 47 ]. The plasma concentration of vitamin D itself was reported to be reduced in these children [ 13 , 14 , 15 ], with a negative correlation between circulating serum vitamin D concentration and CARS scores, suggesting ASD severity to be associated with vitamin D serum levels [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin D deficiency during pregnancy may represent a risk factor for ASD in offspring [ 11 ]. Further, lower levels of vitamin D were reported in ASD children compared with neurotypical controls [ 12 , 13 , 14 ], and vitamin D supplementation was suggested to exert a potential beneficial effect in these children [ 15 ]. However, a clear consensus on the role of vitamin D in the pathogenesis of ASD has not been reached [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the vitamins, minerals, and micronutrients in ANRC-EP have individually been investigated and found to be beneficial in children and/or adults with ASD in randomized, double-blind, placebo-controlled studies. These include studies of Methyl-B12, folinic acid, and trimethylglycine (TMG) [ 6 , 7 , 26 ], high dose folinic acid [ 27 , 28 ], high dose vitamin B6 with magnesium [ 29 ], vitamin D [ 30 – 32 ], high-dose carnitine [ 33 , 34 ], CoQ10 [ 35 ], and high-dose Vitamin C [ 13 , 36 ]. Similarly, Open-label trials of vitamin/mineral supplementation for ASD have reported benefits for vitamin A [ 37 ], iron [ 16 ] and zinc [ 15 ], in children with ASD, and a case study of high dose biotin [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns can be cause by GI issues such as gastroesophageal reflux [ 62 ], avoidant/restrictive food intake disorder [ 88 ] and/or food allergies causing GI inflammation such as eosinophilic esophagitis [ 89 ]. Second, children with ASD are known to be susceptible to vitamin and micronutrient deficiencies, including vitamin D deficiency and insufficiency [ 90 ], vitamin A, cobalamin, zinc and iron deficiency [ 91 ], which can sometimes be secondary to avoidant/restrictive food intake disorder [ 92 ] and can be related to ASD severity [ 91 ]. Thus, the evaluation of the dietary intake is twofold, both to ensure proper nutrition is being consumed and to assure that the child is not being exposed to substances that they might be allergic or sensitive to.…”
Section: Specific Factors To Address In Autism Spectrum Disordermentioning
confidence: 99%
“…Treatment of nutritional deficiencies can be straightforward, while implementing dietary changes can be complicated by behavioral problems [ 28 ]. Preliminary studies suggest that vitamin D [ 90 ] and/or zinc [ 107 ] supplementation might improve ASD symptoms. Treatment of metabolic disorders can be complex [ 108 ] and should be managed by a specialist.…”
Section: Specific Factors To Address In Autism Spectrum Disordermentioning
confidence: 99%